Input and literacy effects in simultaneous and sequential bilinguals: The performance of Albanian–Greek-speaking children in sentence repetition. (April 2020) - Kaltsa, Maria; Prentza, Alexandra; Tsimpli, Ianthi Maria
Aim: The present study examines input and literacy effects in simultaneous and sequential bilinguals with the aim of (a) investigating the differences between bilingual and monolingual populations and (b) disentangling the individual contribution of different factors in bilingual syntactic abilities. Methodology: A sentence repetition task (SRT) in Greek with eight structures (Subject Verb Object [SVO], negative clauses, clitic structures, complement clauses, coordinated sentences, adverbial clauses, wh-questions and relative clauses) was employed. All bilinguals additionally participated in a standardized expressive vocabulary task in Greek to measure their lexical ability. Data: Sixty 8–10-year-old children (20 monolingual, 20 simultaneous and 20 late sequential bilinguals) were tested. Findings: The analysis showed that (a) monolinguals outperform sequential bilinguals in sentence repetition, (b) clitic structures are highly problematic for all participants, (c) vocabulary and syntactic skills are closely related for simultaneous but not for sequential bilinguals, (d) home language practices in the early years affect SRT performance and (e) sequential bilinguals benefit from literacy practices that support syntactic skills in the language tested. Overall, we found that the effect of input overrides the effect of a traditionally categorical factor in bilingualism: age of onset (AoO) of exposure to L2. Originality: The contribution of this study includes (a) the examination of syntactic abilities in bilinguals in connection with language input early in life and at the time of testing, (b) the non-pervasive role of age of exposure to the L2 in SRT performance and (c) the role of literacy measures as key factors affecting syntactic skills in bilinguals. Implications: Quality of input and literacy in particular have been shown to affect bilingual syntactic skills, suggesting that enhancing literacy exposure as a language policy for bilinguals has a significantly positive impact on language development.